Influence of dietary energy levels on reproductive function and fertility in yearling beef heifers - S.D. Utter; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1994)
Fifty-nine heifers were allotted to be fed at two different energy levels. One group gained 1.77 lb/hd/day, and the other 1.25 lb/hd/day. Estrus was synchronized with the MGA/prostaglandin system. After MGA removal, ovarian development was monitored daily by ultrasound (10 per group) until estrous was detected following the PGF injection. Heifers were inseminated artificially based on estrus behavior. Faster gaining heifers had higher final body condition scores and greater changes in body condition score. The high energy diet caused a slight (P=.11) decrease in AI pregnancy rate for purebred heifers.
Keywords: Cattlemen' s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Beef heifers; Energy levels; Ovarian function; Fertility